Unraveling the Host Plant Alternation of Cacopsylla pruni – Adults but Not Nymphs Can Survive on Conifers Due to Phloem/Xylem Composition - Gallinger, Jannicke; Gross, Jürgen (Frontiers in Plant Science, 2018)
Plant sap feeding insects like psyllids are known to be vectors of phloem dwelling bacteria (Candidatus Phytoplasma and Ca. Liberibacter), plant pathogens which cause severe diseases and economically important crop damage. Some univoltine psyllid species have a particular life cycle, within one generation they alternate two times between different host plant species. The plum psyllid Cacopsylla pruni, the vector of European Stone Fruit Yellows (ESFY), one of the most serious pests in European fruit production, migrates to stone fruit orchards (Prunus spp.) for mating and oviposition in early spring. The young adults of the new generation leave the Prunus trees in summer and emigrate to their overwintering hosts like spruce and other conifers. Very little is known about the factors responsible for the regulation of migration, reasons for host alternation, and the behavior of psyllids during their phase of life on conifers. Because insect feeding behavior and host acceptance is driven by different biotic factors, such as olfactory and gustatory cues as well as mechanical barriers, we carried out electrical penetration graph (EPG) recordings and survival bioassays with C. pruni on different conifer species as potential overwintering hosts and analyzed the chemical composition of the respective plant saps. We are the first to show that migrating psyllids do feed on overwintering hosts and that nymphs are able to ingest phloem and xylem sap of coniferous trees, but cannot develop on conifer diet. Analyses of plant saps reveal qualitative differences in the chemical composition between coniferous trees and Prunus as well as within conifer species. These differences are discussed with regard to nutritional needs of psyllid nymphs for proper development, overwintering needs of adults and restriction of Ca. P. prunorum to Prunus phloem.